Diseño conceptual para la producción de desinfectante blanqueador en la microempresa Limpia Fácil (2018)
This graduation project was done for the interest of the Limpia Facil microenterprise to grow up and expand itself in the long term, with the product that generates more sales and profits which is the bleach disinfectant produced in a purely artisanal way, it is a cleaning product based of sodium hypochlorite, contains trisodium phosphate that acts as a bleaching agent. This liquid eliminates bacteria on the surfaces in which it is going to be used. These cleaning products have generated a great boom in the market in recent years, thus emerging multiple microenterprises making this kind of home and industries consumer products. For some time, the bleaching disinfectant production has been carried out by microentrepreneurs artists, evidencing the process technification lack, for this reason it has deficiencies in quality and presentation in the final products not complying with standards requirements like INVIMA and ICONTEC requirements, moving away the possibility of growing up in bigger markets. Due the above, this becomes a challenge for a chemical engineer in which he can make use of his knowledge and research and innovation capacities in the process of technification of the bleaching disinfectant, thus evidencing several opportunities for the possible implementation of the conceptual design by the Limpia Facil microenterprise including product uniformity, quality standards, characterization of raw material, recommendations regarding industrial safety and cost analysis study.